Formulation of Hair Dye from Purple Sweet Potato Extract (Ipomoea batatas (L.) Lam.) - Yolandha Putri; Dini Liya Meirani Simarupang; Romi Ardiansyah; Yenni Mulyani (Hikamatzu | Journal of Multidisciplinary, 2026)
The making of purple sweet potato  extract (Ipomoea batatas (L.) Lam.) namely macerated powder with 96% ethanol extractor 1 night and doing the same way till the solution is colourless. Next, the hair dye is made of formula which consists of purple sweet potato by some concentration. Those are 5, 10, 15. First, at formula 1 pirogalol,  sulfate cuprum, xhantangum are 1%. Second,  at formula 2 pirogalol,  sulfate cuprum,  xhantangum are 2%. Third,  at formula 3 pirogalol,  sulfate cuprum,  xhantangum are 3%. Additionally,  aquadest is used for a solvent. Then,  the colouration is done by submersion during 1-4 hours. The observation is stability on 12 times washing of. Moreover,  the result of research shows that the extract substance of purple purple sweet potato can be used for hair dye. The best dye is got from the formula 3 which consists of purple purple sweet potato 15%,  pirogalol 3%, cuprum II sulfate 3% and xhantangum 3% which produce dark black.